The effect of profitability and liquidity on CSR disclosure and its implication to economic consequences - Dody Hapsoro; Ratna Dwi Sulistyarini (STIE Perbanas Surabaya, 2019)
This study examines the effect of profitability and liquidity on CSR disclosure and its implication on economic consequences. This study was driven by the inconsistency of the results of previous studies in testing the factors that influence the CSR disclosure. This study used the CSR disclosure to measure Corporate Social Responsibility disclosure index (CSRDI) based on the index of the Global Reporting Initiatives G4 Guideline (GRI G4). The results show that profitability has a significant and positive effect on CSR disclosure, while liquidity does not affect CSR disclosure. Furthermore, CSR disclosure has a negative effect on the bid-ask spread, CSR disclosure has a positive effect on trading volume, while CSR disclosure doesn't affect stock price volatility. This study impklies as the following;: companies that have high profitability should have strong commitment to disclose corporate social responsibility because it can help reduce information asymmetry.